The Constitution of the Land Management Circle, United Provinces - Chaturvedi, M. D. (Indian Forester, 1946)
Besides providing technical assistance to private owners in the rehabilitation of their woodland hacked about during the war, the Land Management Circle of the Forest Department, U.P., as constituted on November 1, 1945, envisages the economic utilization of all state lands such as those under railways, roads and canala. In addition, it aims at the progressive acquisition of a million acres of wastelands during the next 10 years for the establishment of fuel and fodder reserves, improvement of grazing grounds and the creation of protective belts to arrest erosion. The elasticity of the scheme which can be expanded as funds permit, the provision for the employment of demobilized army personnel and the integrated utilization of lands to cope with the increasing pressure of population are some of its features which commend themselves.